The timing and extent of acute physiotherapy involvement following lung transplantation: An observational study. (12th March 2018) - Tarrant, Benjamin James; Holland, Anne; Le Maitre, Caitlin; Robinson, Rebecca; Corbett, Monique; Bondarenko, Janet; Button, Brenda; Thompson, Bruce; Snell, Greg
Abstract: Background and purpose: Physiotherapy "standard care" for the acute post lung transplant recipient has not yet been documented. We aimed to analyse how soon patients commence exercise and how much time is dedicated to this during physiotherapy sessions acutely post lung transplantation. Methods: Prospective observational study of bilateral sequential and single lung transplant recipients for any indication, ≥18 years. Participants were observed during 6 physiotherapy sessions: 3 initial and 3 prior to acute inpatient discharge. Duration and content of each session was recorded, consisting of physical exercise and non‐exercise tasks. Results: Thirty participants, 20 male, median age 58.5 (interquartile range 54.5–65.0) were observed over 173 sessions. Chronic obstructive pulmonary disease was the most common transplant indication ( n  = 12, 40%). Bilateral lung transplant was performed in 90% ( n  = 27) of participants. First time to mobilise was 2 (2–3) days. Participants received 14 (12.8–23.8) sessions over 18 (17–31) days. The mean duration of physiotherapy in the initial phase was 107.8 (standard deviation 21.8) min, with 22.9 (7.5) min spent exercising. In the final phase, exercise time increased to 28.1 (11.4) min out of 84.1 (24.6) min. Assessment was the most common non‐exercise component, at 26.6 (7.9) and 22.1 (12.5) min across the three initial and final sessions. Implications for physiotherapy practice: Lung transplant recipients spent 21–34% of observed sessions performing physical exercise beginning 48 hr following surgery. Remaining physiotherapist time was spent on assessment, respiratory interventions, education, and patient‐specific duties. The use of physiotherapy assistants, structured, progressive exercise programs, and continued workplace innovation may enable a higher percentage of physiotherapist supervised physical exercise in the future.